Characteristics and management of follicular events and contact dermatitis in patients using tapinarof cream for the treatment of atopic dermatitis or plaque psoriasis - Linda Stein Gold; Matthew J. Bruno; G. Michael Lewitt; Adelaide A. Hebert (Journal of Dermatological Treatment)
Purpose: Provide insights into the incidence, presentation and management of follicular events and contact dermatitis in patients with plaque psoriasis or atopic dermatitis (AD) treated with tapinarof cream 1%.Materials and methods: Key clinical trial publications for tapinarof were reviewed and augmented with the authors’ opinions based on real-world clinical experience.Results: In the PSOARING and ADORING trials, discontinuation rates due to follicular events and contact dermatitis were low and most patients did not require dose modifications or treatment interruptions. In our experience, which includes the use of tapinarof in combination with other agents, tapinarof is generally well tolerated and if events of folliculitis or contact dermatitis occur, patients can be advised to temporarily discontinue application on affected sites until the event resolves, continuing application to other affected areas and body regions. Education on the correct application of tapinarof is important in the management of psoriasis and AD.Conclusions: Tapinarof is a novel topical treatment option for adults with plaque psoriasis and patients with AD, with no restrictions regarding application sites and duration of use. Follicular events and contact dermatitis associated with tapinarof treatment are generally mild and self-limiting and rarely interfere with therapy.Clinicaltrials.gov numbers: NCT05014568, NCT05032859, NCT05142774, NCT03956355, NCT03983980, NCT04053387